484 Can Respiratory Questionnaire Completion by Parents Obviate the Need for Outpatient Assessment?. (October 2012) - Perrem, LM; O'Neill, MB
Abstract : Background and Aims: Continuing care of asthmatic children is traditionally provided in outpatients settings. This study evaluated the effectiveness of both asthma and upper airway cough syndrome assessment by questionnaire and its acceptability to parents. Methods: The parents of children aged 4–13 years, attending an asthma clinic, were requested to complete the Asthma Control Test (ACT) and Respiratory Assessment Proforma (RAP). The RAP assessed the symptoms of upper airway cough syndrome, asthma medication use and associated risk factors. Parents were asked their views of these assessments as an alternative to attending clinic utilising a Likert questionnaire cuing at 1 not at all and at 6 a lot. All children performed pulmonary function tests at the clinic and these were compared to the ACT scores. The RAP was compared to Physician assessment of Asthma and associated co morbidities. Results: One hundred and nine questionnaires were distributed with 102 fully completed. The M: F was 1.8:1. The mean age was 9.1. Asthma severity was mild in23 (23%), moderate in 59(59%) and severe in 18 (18%).The positive predictive value of ACT versus pulmonary function tests was 89%. The RAP identified 19 (18.6%) children with good asthma control but significant UACS symptoms. Fifty six (55%) parents would utilise the questionnaire to obviate a clinic visit, if rapid access to the clinic was available. Conclusion: Questionnaire assessment can adequately identify the absence of asthma and UACS symptoms in children and is acceptable to more than half of parents attending an asthma clinic.